Prosumer Management In Socio-technical Smart-grid - Rathnayaka, Dinusha; Potdar, Vidyasagar; Ou, Monica; Ou, M. (ACM New York, NY, USA, 2012)
A Smart Grid (SG) achieves bidirectional energy and information flow between the energy users and the utility grid, allowing energy users not only to consume energy, but also to generate the green energy and share the excess with the utility grid and other consumers. This type of energy user who both consumes and generates energy is called a “prosumer”. The sustainability of the SG energy sharing process heavily depends on its participating prosumers, making prosumer management schemes crucial within the SG. In this paper, we review the aspects of managing prosumers in SG, which distinguishes this work from other existing surveys on SG. Based on this review, we outline open research challenges in the field of managing prosumers, which should be further investigated in future researches.